THE PROTECTIVE EFFECT OF SARANG SEMUT (Myrmecodia tuberose) TUBERS INFUSION ON GENTAMICIN-PIROXICAM INDUCED NEPHROTOXICITY IN RATS - Tanti Azizah Sujono (Indonesian Journal of Pharmacy, 2014)
Kidney is very important organ for blood filtration. Impaired renal function often results in chronic kidney disease. Sarang semut (Myrmecodia tuberosa) is traditionally used to cure various diseases. This research was conducted to determine the effect of sarang semut infusion in nephrotoxicity rats models by gentamicin-piroxicam. Thirty male Wistar rats were divided into 6 groups. Group I as normal control (CMC Na was treated orally for 7 days), group II was treated sarang semut infusion dose of 1g/kgBW orally for 7 days, group III as nephrotoxic control was injected by gentamicin 100mg/kgBW intraperitoneally and piroxicam 3.6mg/kgBW orally daily for 7 days and group IV until VI were rats simultaneously treated with sarang semut infusion at the dose of 1, 2, and 4g/kgBW, respectively and induced by gentamicin-piroxicam daily for 7 days. Parameters of kidney function such as serum creatinine and blood urea nitrogen (BUN) levels were measured on day 0 and 7 using spectrophotometer. The rats were then sacrificed, kidneys tissue were removed for examination of renal index and kidney histology. These results showed that sarang semut tubers infusion at the dose of 1, 2, and 4g/kgBW reduced BUN and creatinine levels on induced-nephrotoxic rats. Creatinine level was reduced significantly to 1.76±0.13; 0.86±0.15; 0.60±0.07mg/dL, respectively. The creatinine level of nephrotoxic control was 5.16±0.27mg/dL. BU level decreased significantly to 55.66±6.22; 18.49±2.61; 16.81±1.24mg/dL, respectively. Meanwhile the BUN level of nephrotoxic control was 276.65±50.52mg/dL. Rat histological profile of the three doses tratment showed improvement in renal cell after administration of sarang semut infusion for 7 days.